THE RUSSIAN COMMUNITY IN HANKOU (THE SECOND HALF OF THE XIX - EARLY XX CENTURIES) - Khisamutdinov A.A.; Gao M. (Вестник Брянского государственного университета)
The article reveals the details of the diverse activities of the Russian community in Hankou, one of the largest commercial ports in China open to foreign trade. Russian russians analyze the process of development and formation of Hankou from the first operations of Russian tea merchants in the middle of the XIX century and the opening of factories before the appearance of the Russian concession (1896), then abandoning it after the events of 1917 in Russia. The study shows how the appearance of Russian entrepreneurs in the Chinese port contributed to the development of the city. The opening of trading offices, mechanized enterprises, banks, schools, clubs and a library ensured the development of urban infrastructure, created a comfortable urban environment, activated public life, raised the cultural level, which allowed Hankou to quickly grow from a relatively closed traditional trading port into a major center of international importance. Later, Russian emigration used the successful experience of the Russian community in Hankou, whose residents moved to Harbin, Shanghai, Beijing and other cities in China. Former Consul General A.T. Belchenko played a special role in describing the history of the Russian Hankou. The publication uses sources and literature from Chinese and foreign archives and libraries.